2022
DOI: 10.3389/fmicb.2022.975610
|View full text |Cite
|
Sign up to set email alerts
|

Reappraising host cellular factors involved in attachment and entry to develop antiviral strategies against porcine reproductive and respiratory syndrome virus

Abstract: Porcine reproductive and respiratory syndrome (PRRS), caused by PRRS virus (PRRSV), is a highly contagious disease that brings tremendous economic losses to the global swine industry. As an intracellular obligate pathogen, PRRSV infects specific host cells to complete its replication cycle. PRRSV attachment to and entry into host cells are the first steps to initiate the replication cycle and involve multiple host cellular factors. In this review, we recapitulated recent advances on host cellular factors invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 154 publications
0
4
0
Order By: Relevance
“…PRRSV is one of the most important pathogens in the pig industry, which causes huge economic losses worldwide. However, current PRRS vaccines cannot provide effective protection for the disease, and there are even no feasible drugs for the therapy [ 13 , 28 ]. In our study, we found a safe botanical compound called bergamottin, which is derived from citrus fruits and showed an inhibitory effect on PRRSV replication in vitro ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…PRRSV is one of the most important pathogens in the pig industry, which causes huge economic losses worldwide. However, current PRRS vaccines cannot provide effective protection for the disease, and there are even no feasible drugs for the therapy [ 13 , 28 ]. In our study, we found a safe botanical compound called bergamottin, which is derived from citrus fruits and showed an inhibitory effect on PRRSV replication in vitro ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies have suggested several host cellular molecules as potential entry mediators and receptors for PRRSV such as CD169, non-muscle myosin heavy chain 9 (MYH9), heparan sulphate, vimentin, DC-SIGN (CD209), CD151, and CD163 [13][14][15]. However, research involving genetically modified pigs demonstrated that CD163 is the only essential and sufficient receptor for PRRSV infection [13][14][15]. The exact function of CD163 remains uncertain, but it has been suggested that CD163 cooperates with CD169 in facilitating viral internalization [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, research involving genetically modified pigs demonstrated that CD163 is the only essential and sufficient receptor for PRRSV infection [13][14][15]. The exact function of CD163 remains uncertain, but it has been suggested that CD163 cooperates with CD169 in facilitating viral internalization [13][14][15]. A role of CD163 in mediating viral membrane fusion with the target cells and viral uncoating has also been proposed [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disease affects pigs of all ages and is characterized by reproductive failures in sows during late-term gestation, including high rates of abortions, mummified fetuses, and post-weaning mortality due to the birth of weak piglets, with perinatal mortality reaching up to 70%. Additionally, it causes respiratory disease in both piglets and adult swine [ 3 , 5 , 6 ]. PRRSV has shown a high capacity for infection and transmission through the oronasal and reproductive routes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%